The Death Scene in the "Ayniyah" Poems of Abi Thuayib Al-Huthali and Suda bint Shamardal: A Contrastive Study (Journal of the College of Education for Women, 2022)
This study is an objective literary study of the poems of Abu Dhu'ayb Al-Hudhali and Su'da Bint Al-Shamrdal. It aims to shed light on the philosophy of death in the poems, and the way this philosophy is treated by both poets. Thus, the main prominent poetic images have been addressed and the outstanding ones have been singled out. The study further investigates the intertextuality with other poetic verses and Quranic verses and reviews the deviation in their semantic, syntactic, and phonetic types. The study adopts the historical approach to examine the occasion of the poems by referring to several historical sources that indicate the seniority. It also adopts the and descriptive-analytical approach represented by the use of content analysis to investigate the most prominent themes and literary features. The study has concluded that Abu Dhu'ayb’s creativity in drawing literary images is due to being one of the - "Hudhalis" - those who follow the approach of drawing literary images. The poems were overflowing with sincere feelings. However, Su'da’s feelings were clearer, as the literary vocabularies and images played a major role in adding a sense of sadness and affliction. Moreover, the study has concluded that Su'da's poem is the earlier, as it did not witnessed Islam as is the case with Abu Dhu'ayb who contemprorarized the wise kalihs.